STRENGTHENING THE ORGANIC FARMING ECOSYSTEM AND DIGITAL MARKETING FOR RICE COMMODITIES PURBAYA TANI MANDIRI GROUP IN PURWABAKTI VILLAGE, PAMIJAHAN, BOGOR - Harbani, Arif; Supriyatna, Alam; Junaedi, Dadang; Zulfikar, Daud; Zein, Aliyatu Shabrina (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
This community service program (PKM) primarily aims to improve the economic welfare of the Purbaya Tani Mandiri (PTM) Farmer Group in Purwabakti Village, Bogor. The group, consisting of 40 members and managing 17.93 hectares of land, faces a crucial problem: the low selling price of organic rice (equivalent to non-organic) due to the lack of official certification and limitations in digital marketing. The program offers an integrated solution through education on securing product legality (Organic Certification and P-IRT/Home Industry Food Permit) and digital marketing training, which includes brand development, visual content, and the use of leading e-commerce platforms (Shopee and Tokopedia). The method used is a participatory approach with five stages: preparation, bureaucratic education, program execution, partner participation, and evaluation. The targeted outcomes of the program are an increase in product selling value, expansion of market reach to a national scale, and a significant improvement in farmer income.